Molecular and Epidemiological Features of Peste des Petits Ruminants Outbreak during Endemic Situation. Issue 4 (2016) - Abubakar, Muhammad; Manzoor, Shumaila; Wensman, Jonas Johansson; Torsson3, Emeli; Ali, Qurban; Munir, Muhammad
No abstract available